Frost-seeding of summer turnip rape in the subarctic - Sparrow, Stephen D.; Knight, Charles W. (Canadian Journal of Plant Science, 1992)
Previous research has indicated that spring-planted summer turnip rape (Brassica rapa L.) can produce good seed yields with high oil content in subarctic Alaska. However, short growing seasons often prevent seeds from reaching full maturity, resulting in high proportions of green seeds and lowered market quality. In an attempt to allow summer turnip rape seedlings to begin growth earlier in the growing season, we planted the seeds in frozen soil in late fall and early spring. Fall seeding of summer turnip rape always resulted in low plant populations, low seed yields, and high percentages of green seeds. Percentages of green seeds were highly variable and early spring seedings did not result in significantly lower percentages of green seeds than conventional (May) seedings. The effects of early spring frost-seeding on plant populations and seed yields were variable but only rarely did early spring seeding produce significantly higher seed yields than conventional seeding. Planting into barley (Hordeum vulgare L.) stubble resulted in poor stands which produced low seed yields. This study did not indicate any advantage from fall planting of summer turnip rape. Results from spring frost-seeding were not consistent; therefore, this practice cannot be recommended until these inconsistencies are better understood.Key words: Frost-seeding, summer turnip rape, subarctic, Alaska